Dopamine receptor type 2 (DRD2) inhibits migration and invasion of human tumorous pituitary cells through ROCK-mediated cofilin inactivation. Issue 2 (28th October 2016) - Peverelli, E.; Giardino, E.; Treppiedi, D.; Locatelli, M.; Vaira, V.; Ferrero, S.; Bosari, S.; Lania, A.G.; Spada, A.; Mantovani, G.
Highlights: DRD2 agonist inhibits NFPT cell migration and invasion. DRD2 agonist increases cofilin phosphorylation (inactivation) in NFPT cells. The invasiveness of pituitary tumors is promoted by the activation of cofilin. Cofilin phosphorylation might be a novel biomarker for pituitary tumors invasiveness. Abstract: Non-functioning pituitary tumors (NFPTs) frequently present local invasiveness. Dopamine receptor 2 (DRD2) agonists are the only medical therapy that induces tumor shrinkage in some patients. Invasion requires cytoskeleton rearrangements that are tightly regulated by cofilin pathway, whose alterations correlate with invasion in different tumors. We investigated the effect of DR2D agonist on NFPT cells migration/invasion and the molecular mechanisms involved. We demonstrated that DRD2 agonist reduced migration (−44 ± 25%, p < 0.01) and invasion (−34 ± 6%, p < 0.001) and increased about 4-fold Ser3-phosphorylated inactive cofilin (P-cofilin) in NFPT cells. These effects were abolished by inhibiting ROCK, a kinase that phosphorylates cofilin. The overexpression of wild-type or phosphodeficient S3A-cofilin increased HP75 cells migration (+49 ± 6% and +57 ± 9% vs empty vector, respectively, p < 0.05), while phosphomimetic mutant had no effect. Interestingly, P-cofilin levels were lower in invasive vs non-invasive tumors by both western blot (mean P-cofilin/total cofilin ratio 0.77 and 1.93, respectively, p < 0.05) and immunohistochemistry (mean percentage of P-cofilin positive cells 17.6 and 45.7, respectively, p < 0.05). In conclusion, we showed that the invasiveness of pituitary tumors is promoted by the activation of cofilin, which can be regulated by DRD2 and might represent a novel biomarker for pituitary tumors' invasive behavior.